Case report: Magnetocardiography as a potential method of therapy monitoring in amyloidosis - Golpour, Ainoosh; Suwalski, Phillip; Landmesser, Ulf; Heidecker, Bettina (Frontiers in Cardiovascular Medicine, 2023)
Amyloidosis is characterized by a disorder of protein conformation and metabolism, resulting in deposits of insoluble fibrils in various organs causing functional disturbances. Amyloidosis can also affect the heart. Cardiac amyloidosis tends to have a poor prognostic outcome if diagnosed at a late stage. Therefore, early diagnosis and initiation of therapy as well as monitoring of treatment response are crucial to improve outcomes and to learn more about its pathophysiology and clinical course. We present an 83-year-old woman with cardiac transthyretin amyloidosis (ATTR) who was treated with tafamidis. The patient significantly improved 18 months after initiation of therapy with regards to exercise capacity and quality of life. In addition to standard diagnostic methods, we used magnetocardiography (MCG) to monitor potential treatment response by detecting changes in the magnetic field of the heart. MCG is a non-invasive method that detects the cardiac magnetic field generated by electrical currents in the heart with high sensitivity. We have recently shown that this magnetic field changes in various types of cardiomyopathies may be used as a non-invasive screening tool. We determined previously that an MCG vector ≥0.052 was the optimal threshold to detect cardiac amyloidosis. The patient's MCG was measured at various time points during therapy. At the time of diagnosis, the patient's MCG vector was 0.052. After starting therapy, the MCG vector increased to 0.090, but improved to 0.037 after 4 months of therapy. The MCG vector reached a value of 0.017 after 5 months of therapy with tafamidis, and then increased slightly after 27 months to a value of 0.027 (<0.052). Data from this case support our previous findings that MCG may be used to monitor treatment response non-invasively. Further research is needed to understand the unexpected changes in the MCG vector that were observed at the beginning of therapy and later in the course. Larger studies will be necessary to determine how these changes in the electromagnetic field of the heart are related to structural changes and how they affect clinical outcomes.